Gangguan Berbahasa Tataran Fonologis pada Penderita Autisme Tokoh Hendra dalam Film My Idiot Brother - Ajeng Nabilla Anugrah; Nadya Tri Ananda; Muhammad Raihan Ramadhan; Fatmawati Fatmawati (UIR Press, 2023)
This study aims to examine language disorders in people with autism in the character Hendra in the film My Idiot Brother because these disorders can affect a person's speaking ability, because people with autism cannot even say a word at the age of one. In researching literary works, qualitative research data were obtained by combining data from the film My Idiot Brother which is related to language disorders of people with autism. In addition, researchers also studied various other sources, such as journal articles and other research as information material about language disorders of people with autism. The research results obtained by researchers at the phonological level of language disorders in the character Hendra in the film My Idiot Brother are (1) the omission of phonemes. The form of mistakes that occur in Hendra's character is: the utterances issued by Hendra's character sometimes change. (2) irregularity. In the story of the character Hendra in the film My Idiot Brother, the pronunciation of the word is irregular, including [robot] becomes [obot], [make] becomes [uat], and the word [ayok] becomes [aiyo].